Identification of serum proteins involved in pancreatic cancer cachexia - Felix, Klaus M.; Fakelman, Frederik; Hartmann, Daniel; Giese, Nathalia; Gaida, Matthias; Schnölzer, Martina; Flad, Thomas; Büchler, Markus W.; Werner, Jens (Life sciences, 2011)
Aims - Treatment of cachexia requires pharmacological intervention which, in turn, requires knowledge of the mediators and processes. Cachexia markers that are specifically expressed in pancreatic cancer and secreted into the blood circulation have yet to be identified. The aim of our study was to investigate the serum protein profiles and protein alterations associated with cachexia and to identify potential disease protein biomarkers indicative for this syndrome. - Main methods - Serum samples from cachectic and non-cachectic patients undergoing pancreatic cancer (PaCa) surgery and controls were investigated by Surface Enhanced Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (SELDI-TOF-MS). The identity of detected discriminatory markers was determined by a combination of protein fractionation, chromatographic purification steps, gel electrophoresis, and mass spectrometry. - Key findings - Using Cu-IMAC array and CM-10 array based SELDI-TOF-MS. we identified eleven up- and four down-regulated proteins associated with cachexia. CiphergenExpress analysis revealed four disease-associated protein features (38559Da, 9138Da, 8925Da and 3358Da) that were elevated by a factor of 2.3, 1.7, 1.4 and 1.4, respectively. Zinc-α2-glycoprotein (ZAG), apolipoproteins apo C-II and apo C-III and glucagon-like peptide-1 (GLP-1) were identified as markers for PaCa-associated cachexia syndrome. ZAG levels were additionally evaluated in serum and tissue samples by ELISA and immunohistochemistry and the obtained data confirmed the SELDI-TOF-MS results. - Significance - The identified proteins could be routinely and reliably measured in the serum of patients and provide an elegant non-invasive approach for early diagnosis of cachectic pancreatic cancer patients. Controlling ZAG and GLP-1 activity could be beneficial in the management of cancers and cachexia-induced conditions.
Available online 19 November 2010
Gesehen am 05.05.2022